Are Prisoners More Psychopathic than Non-forensic Populations? Profiling Psychopathic Traits among Prisoners, Community Adults, University Students, and Adolescents. Issue 2 (1st February 2021) - Boduszek, Daniel; Debowska, Agata; Sherretts, Nicole; Willmott, Dominic; Boulton, Mike; Kielkiewicz, Krzysztof; Popiolek, Katarzyna; Hyland, Philip
ABSTRACT: The aim of this study was to compare prisoners ( n = 772), community adults ( n = 1201), university students ( n = 2080), and adolescents ( n = 472) on four sets of psychopathic traits (affective responsiveness, cognitive responsiveness, interpersonal manipulation, and egocentricity), using a psychopathy measure which does not index criminal/antisocial behavior – the Psychopathic Personality Traits Scale. Another aim was to examine patterns of co-occurrence between psychopathic personality traits among offending and non-offending populations. ANOVA results indicated significant differences between the four groups on all PPTS dimensions. Adolescents demonstrated greater deficits in affective and cognitive responsiveness than the remaining groups of participants. Prisoners had elevated deficits in cognitive responsiveness, compared with university students and community adults. University students scored higher on interpersonal manipulation than adolescents and prisoners, and higher on egocentricity than community adults and prisoners. Latent profile analysis revealed four distinct classes of psychopathic traits among all samples, although not all classes were qualitatively equivalent across samples. Low psychopathy groups were identified for all samples. There were clear high psychopathy groups for prisoners and university students, with approximately 7% of prisoners and students belonging in the groups. This finding indicates that past research could have over-estimated the prevalence of psychopathy in forensic populations due to inclusion of criminal behavior items in psychopathy assessment.